Global trends and research hotspots of PCSK9 and cardiovascular disease: a bibliometric and visual analysis - Tang, Masong; Yang, Sen; Zou, Junying; Li, Meng; Sun, Yan; Wang, Mengqi; Li, Wanhan; He, Junhui; Chen, Ying; Tang, Zhanyou (Frontiers in Cardiovascular Medicine, 2024)
Background: Cardiovascular disease (CVD) is a prevalent non-communicable disease globally and holds the position of being the primary cause of mortality worldwide. Consequently, considerable focus has been directed towards the prevention and management of CVD. PCSK9, a frequently targeted element in the treatment and prevention of CVD, can reduce cardiovascular risk by effectively lowering lipid levels even in the context of statin therapy. It also exhibits substantial potential in the diagnosis and treatment of familial hypercholesterolemia from genetic aspects. This bibliometric study aims to analyze and visualize the global trends and emerging hotspots of PCSK9 and CVD researches and provide researchers with new perspectives in further studies. Methods: The data was obtained from the Web of Science Core Collection database. A total of 2474 publications related to PCSK9 and CVD published between January 2006 and July 2023 were included. The VOSviewer was used to analyze most-cited references, co-authorship, co-citation, co-occurrence and generate a collaborative network map of authors, countries, and institutions. CiteSpace was used to analyze author and institution centroids, keyword bursts, and timeline graphs. Result: A total of 2474 articles related to CVD and PCSK9 were included. The number of articles and citations show an increasing trend from year to year. Publications were mainly from the United States. The most active institution was Amgen Inc.. Watts, Gerald F. was the most prolific author. Atherosclerosis was the most published journal. Literature co-citation and keyword co-occurrence revealed that early studies focused on the lipid-lowering effects of PCSK9 inhibitors in the context of statins therapy, long-term efficacy, adverse effects, LDLR, diagnosis and treatment of familial hypercholesterolemia. In recent years, myocardial ischemic protection, CRISPR-based editing, and new therapeutic strategies for arteriosclerotic cardiovascular disease have gotten wide attention. The protein convertase, inflammation, beta-polyacetate, and inclisiran may be the important future research directions.This study analyses the current status and global trends in the CVD and PCSK9 studies comprehensively, which may provide researchers and policymakers with new and comprehensive perspectives on in this field of research.